Circumferential and functional re‐entry of in vivo slow‐wave activity in the porcine small intestine. Issue 5 (12th March 2013) - Angeli, T. R.; O'Grady, G.; Du, P.; Paskaranandavadivel, N.; Pullan, A. J.; Bissett, I. P.; Cheng, L. K.
Abstract Background Slow‐waves modulate the pattern of small intestine contractions. However, the large‐scale spatial organization of intestinal slow‐wave pacesetting remains uncertain because most previous studies have had limited resolution. This study applied high‐resolution (HR) mapping to evaluate intestinal pacesetting mechanisms and propagation patterns in vivo. Methods HR serosal mapping was performed in anesthetized pigs using flexible arrays (256 electrodes; 32 × 8; 4 mm spacing), applied along the jejunum. Slow‐wave propagation patterns, frequencies, and velocities were calculated. Slow‐wave initiation sources were identified and analyzed by animation and isochronal activation mapping. Key Results Analysis comprised 32 recordings from nine pigs (mean duration 5.1 ± 3.9 min). Slow‐wave propagation was analyzed, and a total of 26 sources of slow‐wave initiation were observed and classified as focal pacemakers (31%), sites of functional re‐entry (23%) and circumferential re‐entry (35%), or indeterminate sources (11%). The mean frequencies of circumferential and functional re‐entry were similar (17.0 ± 0.3 vs 17.2 ± 0.4 cycle min−1; P = 0.5), and greater than that of focal pacemakers (12.7 ± 0.8 cycle min−1; P < 0.001). Velocity was anisotropic (12.9 ± 0.7 mm s−1 circumferential vs 9.0 ± 0.7 mm s−1 longitudinal; P < 0.05), contributing to the onset and maintenance of re‐entry. Conclusions & Inferences This study has shown multiple patterns of slow‐wave initiation in the jejunum of anesthetized pigs. These results constitute the first description and analysis of circumferential re‐entry in the gastrointestinal tract and functional re‐entry in the in vivo small intestine. Re‐entry can control the direction, pattern, and frequency of slow‐wave propagation, and its occurrence and functional significance merit further investigation.